Interpretation possibilities of Middle Neolithic cave usage patterns - Gizella Kovács (Dissertationes Archaeologicae: Ex Instituto Archaeologico Universitatis de Rolando Eötvös Nominatae)
The more than 150-year research of the Baradla Cave in Aggtelek continued with a rescue excavation in 2019, carried out by a team from the Institute of Archaeological Sciences of the Eötvös Loránd University, and reaching the more difficult-to-access inner parts of the cave system. This paper presents the preliminary results of the evaluation of the pottery, stone and animal bone record of the Middle Neolithic Bükk culture, collected during this excavation. Outlining the special natural atmosphere of the cave and surveying its unusual effect on the people venturing there represent a pivotal addition enabling the contextual interpretation of the finds. In addition, a brief overview is given of the diverse ways of how caves were used throughout Europe, organised according to three main aspects (economic, burial, and ritual), which may help get one closer to understanding the prehistoric use of the Baradla Cave.